Monitoring for respiratory viruses among wild canids, Texas - Lyudmyla V. Marushchak; Laura A. Pulscher; Judith U. Oguzie; Diego B. Silva; Kenneth A. Waldrup; Douglas M. Watts; Gregory C. Gray (One Health)
The cross-species transmission of respiratory viruses such as SARS-CoV-2 and avian influenza underscores the need for novel respiratory virus surveillance at the human-animal interface. In this 2023 pilot study we examined oral and rectal swab samples from 15 deceased wild animals for novel respiratory viruses. We used virus molecular techniques, culture and next-generation nucleotide sequencing to search for and characterize viruses in the Coronaviridae and Orthomyxoviridae families. Through these activities we detected and characterized one canine coronaviruses (CCoVs) each from a gray fox (Urocyon cinereorgenteus) and a feral dog (Canis lupus familiaris). The gray fox CCoV sequence clustered with other CCoVs reported in other canids from other regions of the world. The feral dog CCoV sequence was closely related to CCoVs reported in Brazil and the United Kingdom. This pilot study demonstrated the usefulness of a noninvasive monitoring approach in detecting and characterizing respiratory viruses among wild canids.